Child Sexual Violence and the Violation of Human Rights: The Darkest Side of Law Enforcement in Indonesia - Wibowo, Seno Adhi (Faculty of Law Universitas Negeri Semarang, 2020)
The rise of news in the media related to sexual violence against children is a surprise to the community. The perpetrators actually come from the closest people like father, uncle, grandfather. Although this has been regulated in the Law on Child Protection, but in fact this crime continues. If not handled seriously, sexual violence against children can have a broad social impact on the community. Handling and healing psychological trauma due to sexual violence must receive great attention from all parties involved. This paper intends to identify the relationship between sexual violence against children with human rights violations.